Reversing bone loss by directing mesenchymal stem cells to bone. (4th October 2013) - Yao, Wei; Guan, Min; Jia, Junjing; Dai, Weiwei; Lay, Yu‐An E.; Amugongo, Sarah; Liu, Ruiwu; Olivos, David; Saunders, Mary; Lam, Kit S.; Nolta, Jan; Olvera, Diana; et al.
Abstract: Bone regeneration by systemic transplantation of mesenchymal stem cells (MSCs) is problematic due to the inability to control the MSCs' commitment, growth, and differentiation into functional osteoblasts on the bone surface. Our research group has developed a method to direct the MSCs to the bone surface by conjugating a synthetic peptidomimetic ligand (LLP2A) that has high affinity for activated α4β1 integrin on the MSC surface, with a bisphosphonates (alendronate) that has high affinity for bone (LLP2A‐Ale), to direct the transplanted MSCs to bone. Our in vitro experiments demonstrated that mobilization of LLP2A‐Ale to hydroxyapatite accelerated MSC migration that was associated with an increase in the phosphorylation of Akt kinase and osteoblastogenesis. LLP2A‐Ale increased the homing of the transplanted MSCs to bone as well as the osteoblast surface, significantly increased the rate of bone formation and restored both trabecular and cortical bone loss induced by estrogen deficiency or advanced age in mice. These results support LLP2A‐Ale as a novel therapeutic option to direct the transplanted MSCs to bone for the treatment of established bone loss related to hormone deficiency and aging. Stem Cells 2013;31:2003‐2014